A comparison between heart rate and heart rate variability as indicators of cardiac health and fitness - Grant, Catharina C.; Murray, Carien; Janse Van Rensburg, Dina C.; Fletcher, Lizelle (Frontiers in Physiology, 2013)
Quantification of cardiac autonomic activity and control via heart rate (HR) and heart rate variability (HRV) is known to provide prognostic information in clinical populations. Issues with regard to standardisation and interpretation of HRV data make the use of the more easily accessible HR on its own as an indicator of autonomic cardiac control very appealing. The aim of this study was to investigate the strength of associations between an important cardio vascular health metric such as VO2max and the following: HR, HRV indicators and heart rate normalised HRV indicators. A cross sectional descriptive study was done including 145 healthy volunteers aged between 18 and 22 years. HRV was quantified by time domain, frequency domain and Poincaré plot analysis. Indirect VO2max was determined using the Multistage Coopers test. The Pearson correlation coefficient was calculated to quantify the strength of the associations. Both simple linear and multiple stepwise regressions were performed to be able to discriminate between the role of the individual indicators as well as their combined association with VO2max. Only HR, RR interval and pNN50 showed significant (p<0.01, p<0.01 and p=0.03) correlations with VO2max. Stepwise multiple regression indicated that, when combining all HRV indicators the most important predictor of cardio vascular fitness as represented by VO2max, is HR. HR explains 17% of the variation, while the inclusion of HF (high frequency HRV indicator) added only an additional 3.1% to the coefficient of determination. Results also showed when testing the normalised indicators, HR explained of the largest percentage of the changes in VO2max (16.5%). Thus HR on its own is the most important predictor of changes in an important cardiac health metric such as VO2max. These results may indicate that during investigation of exercise ability (VO2max) phenomena, quantification of HRV may not add significant value.